Pharmacists' impact on opportunistic infection prophylaxis in patients with HIV/AIDS. Issue 4 (December 2016) - Schatz, K.; Guffey, W.; Maccia, M.; Templin, M.; Rector, K.
Summary: Pharmacists have demonstrated a positive impact on the care of patients with human immunodeficiency virus/acquired immunodeficiency syndrome through enhancing patient outcomes associated with antiretroviral therapy. This pre- and postintervention study assessed the impact of pharmacist intervention on improving the use of prophylactic medications for opportunistic infections (OI). Of the 139 patients screened, 42 patients were included in the prospective intervention group. A total of 27 interventions were made on 15 patients, and 24 recommendations (89%) were accepted by providers. Compared with the retrospective control group, prescribing of OI prophylaxis increased from 58% to 93% ( P <0.001) with the addition of pharmacist intervention.